Anesthesia information management: clinical decision support. Issue 6 (December 2017) - Freundlich, Robert E.; Ehrenfeld, Jesse M.
Abstract : Purpose of review: Perioperative informatics tools continue to be developed at a rapid pace and offer clinicians the potential to greatly enhance clinical decision making. The goal of this review is to bring the reader updates on perioperative information management and discuss future research directions in the field. Recent findings: Clinical decision support tools become more timely, accurate, and, in some instances, have been shown to improve patient outcomes. When correctly implemented, they are critical tools for optimization of perioperative care. Summary: Perioperative informaticians continue to test new and innovative ways to enhance the delivery of anesthesia care, improving the safety and efficacy of perioperative management. Future work will continue to refine tools to ensure that perioperative informatics provides clinicians timely and accurate feedback, with demonstrable evidence that a decision support system improves patient outcomes.